INTERVAL OPTIMIZATION OF GH4169 MILLING PROCESS PARAMETERS FOR SURFACE RESIDUAL STRESS - HUAI WenBo; SHI YaoYao; DONG XuLiang (Jixie qiangdu)
In order to obtain the ideal surface residual stress of GH4169 milling surface,the optimal interval division method of milling process parameters was proposed,and the orthogonal test of GH4169 milling was designed.The order of the influence of the process parameters on the residual stress was determined by the experiment results and the change trend of the residual stress with the increasing of the process parameters was analyzed.The optimal intervals of process parameters were determined according to the proposed method,and the reliability of the optimized interval was verified by experiments.